Peran Ukuran Perusahaan Dalam Memoderasi Profitabilitas Terhadap Harga Saham Perusahaan Sektor Energi: The Moderating Role of Company Size in the Relationship Between Profitability and Energy Sector Stock Prices - Muhammad Muhammad; Dade Nurdiniah; Sri Yuli Ayu Putri; Zalzabilla Putri Ekawati (Universitas Sulawesi Barat, 2026)
This study aims to analyze the size of companies in moderating profitability against the stock prices of companies in the energy sector for the period 2019 to 2023. The data used in this study is secondary data obtained through observation at the www.idx.co.id site and analyzed using SPSS. The analysis methods applied include multiple linear regression tests and Moderated Regression Analysis (MRA). Sampling was carried out by the purposive sampling method, resulting in a total of 45 observations. The results show that the profitability proxied by Return on Assets (ROA), Return on Equity (ROE) and Net Profit Margin (NPM) has an effect on the stock price, and the size of the company is not able to moderate the effect of ROA, ROE, and NPM on the stock price.